Interpretation Biases in Pain: Validation of Two New Stimulus Sets - Gaffiero, Daniel; Staples, Paul; Staples, Vicki; Maratos, Frances A. (Frontiers in Psychology, 2022)
Adults with chronic pain interpret ambiguous information in a pain and illness related fashion. However, limitations have been highlighted with traditional experimental paradigms used to measure interpretation biases. Whilst ambiguous scenarios have been developed to measure interpretation biases in adolescents with pain, no scenario sets exist for use with adults. Therefore, the present study: i) sought to validate a range of ambiguous scenarios suitable for measuring interpretation biases in adults, whilst also allowing for two response formats (forced-choice and free response); and ii) investigate paradigm efficacy, by assessing the effects of recent pain experiences on task responding. A novel ambiguous scenarios task was administered to adults (N = 241). Participants were presented with 62 ambiguous scenarios comprising 42 that could be interpreted in a pain/pain-illness or non-pain/non-pain illness manner: and 20 control scenarios. Participants generated their own solutions to each scenario (Word Generation Task), then rated how likely they would be to use two researcher-generated solutions to complete each scenario (Likelihood Ratings Task). Participants also rated their subjective experiences of pain in the last three months. Tests of reliability, including inter-rater agreement and internal consistency, produced two ambiguous scenario stimulus sets containing 18 and 20 scenarios, respectively. Further analyses revealed adults who reported more recent pain experiences were more likely to endorse the pain/pain-illness solutions in the Likelihood Ratings Task. This study provides two new stimulus sets for use with adults (including control items) in pain research and/or interventions. Results also provide evidence for a negative endorsement bias in adults.